Current status of water-related planning for climate change adaptation in the Spree river basin, Germany - S. Arndt; S. Heiland (Natural Hazards and Earth System Sciences)
Fuelled by climate change, low flows, heavy rain and flooding will likely intensify in the future, adding to the pressures experienced by rivers in western and central Europe in recent decades. To meet these challenges, comprehensive water-related adaptation to climate change is indispensable. Based on the case study of the Spree river basin in Germany, this study analysed legally defined plans for water management, spatial planning and landscape planning for their current status of integrated climate change adaptation. To pre-structure the document analysis, eight water management fields of action for adaptation to climate change were identified using official recommendations for action. A total of 39 % of the 28 plans analysed specify objectives and measures for adapting to climate change. Of these, 55 % address the diverse impacts of climate change in a more comprehensive way, including prevention and mitigation of droughts and floods, as well as protection of water ecosystems and groundwater resources. Filling these planning gaps may include more frequent updating of plans, a greater focus on evidence from informal plans, multifunctional measures, and the adaptation of best-practice examples for the systematic integration of climate change impacts and adaptation. Planning and implementing comprehensive climate change adaptation will strengthen the resilience of ecosystems and secure human livelihoods.